2017
DOI: 10.1371/journal.pone.0183881
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and self-rated health in East Asian countries: Comparison among South Korea, China, Japan, and Taiwan

Abstract: There have been conflicting findings regarding the relationship between body mass index (BMI) and self-rated health (SRH) worldwide. The purpose of this study was to examine the association between BMI and SRH by comparing its relationship in four East Asian countries: South Korea, China, Japan, and Taiwan. Using data from the East Asian Social Survey, the relationship between weight status and SRH status was investigated and compared between four countries, China, Japan, South Korea, and Taiwan. An ordinal lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 35 publications
(69 reference statements)
4
29
0
1
Order By: Relevance
“…Only one previous study was based on Korean. Noh et al assessed the relationship between BMI categorized as WHO Asian classification and SRH scores, and SRH scores were the highest in the normal-weight (18.5-22.9 kg/m 2 ) [23]. Compared to normal-weight, the odds ratio (OR) of poor SRH score was 1.60 in underweight, 1.08 in overweight, 1.72 in obese, and 3.97 in severely obese.…”
Section: Discussionmentioning
confidence: 99%
“…Only one previous study was based on Korean. Noh et al assessed the relationship between BMI categorized as WHO Asian classification and SRH scores, and SRH scores were the highest in the normal-weight (18.5-22.9 kg/m 2 ) [23]. Compared to normal-weight, the odds ratio (OR) of poor SRH score was 1.60 in underweight, 1.08 in overweight, 1.72 in obese, and 3.97 in severely obese.…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, similar to in Korea, underweight women view themselves as normal or overweight [ 28 ], and a high percentage of normal weight women believed themselves to be overweight [ 29 ]. In summary, many studies reported body image discrepancy, the pattern of which varies by different cultures and countries [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…These values are higher than those reported previously for similarly aged Japanese elderly people (53.5%, 76.2%, and 27.9%, respectively, for elderly people aged 70-79 years) 17) . A possible explanation of this result can be that Taiwanese people have higher proportions of obese and severely obese (32.7%) compared to Japanese people (19.4%) 19) , but further research is required to confirm this possibility. Moreover, our findings indicated that the weight, muscle mass, and SMI were lower, while the age and body fat were higher in the LS group than in the non-LS group.…”
Section: Discussionmentioning
confidence: 96%